2018
DOI: 10.1038/s41477-018-0323-6
|View full text |Cite|
|
Sign up to set email alerts
|

Liriodendron genome sheds light on angiosperm phylogeny and species–pair differentiation

Abstract: The genus Liriodendron belongs to the family Magnoliaceae, which resides within the magnoliids, an early diverging lineage of the Mesangiospermae. However, the phylogenetic relationship of magnoliids with eudicots and monocots has not been conclusively resolved and thus remains to be determined1–6. Liriodendron is a relict lineage from the Tertiary with two distinct species—one East Asian (L. chinense (Hemsley) Sargent) and one eastern North American (L. tulipifera Linn)—identified as a vicariad species pair. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
256
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(307 citation statements)
references
References 70 publications
38
256
3
Order By: Relevance
“…This contrasts with recent studies in magnoliids (Chaw et al 2019;Chen et al 2019), where the authors found WGD with lower Ks values (thus potentially more recent), and hypothesized them to be shared in magnoliids and thus older than the divergence between Lauraceae and Magnoliaceae.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…This contrasts with recent studies in magnoliids (Chaw et al 2019;Chen et al 2019), where the authors found WGD with lower Ks values (thus potentially more recent), and hypothesized them to be shared in magnoliids and thus older than the divergence between Lauraceae and Magnoliaceae.…”
Section: Resultscontrasting
confidence: 99%
“…Scaffolds longer than 100kb totaled 646.64Mb (98.45% of the total length). This level of contiguity is similar to the one obtained in Liriodendron chinensis (N50=3.5 Mb (Chen et al 2019)) but smaller than obtained in Cinnamomum kanehirae (N50=50.4Mb after Hi-C scaffolding (Chaw et al 2019), and better than other genomes assembled at scaffold-level (e.g. (Yang et al 2018;Arimoto et al 2019;Zhang et al 2019)).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Continuity and completeness are important indicators of genome assembly. PacBio-based genome assembly plus error corrections based on Illumina data could greatly improve continuity and completeness [56][57][58][59] . Our genome assembly of I. indigotica by this strategy showed a highly resolved result with an N50 = 1.22 Mb and longest contig length = 8.99 Mb.…”
Section: Discussionmentioning
confidence: 99%